Improving Workplace and Societal Cybersecurity via Post-Secondary General Education (Journal of The Colloquium for Information Systems Security Education, 2023)
Everyone has a role to play in cybersecurity and cyber risk management, but people without security backgrounds seldom understand—let alone accept or endorse—such roles. Public and private organizations face common challenges in facilitating more secure behaviors among employees. As part of their missions, most colleges and universities in the United States have general education programs that aim to instill certain competencies and characteristics in all graduates (for individual and greater good). This paper proposes that a cybersecurity general education course could help improve common workplace challenges in cybersecurity training and awareness, and that such a course could align with each institution’s general education goals to benefit not only graduates but also communities and society writ large.
Keywords: cybersecurity education; risk management; general education; information security; computer security